THE USE OF ENGLISH AS A LINGUA FRANCA IN TEACHING THAI STUDENTS: THE PERSPECTIVES FROM INDONESIAN TEACHERS - Suminto, Elisabeth Avryanne; Ena, Ouda Teda (Premise: Journal of English Education and Applied Linguistics, 2024)
As the number of non-native speakers of English is increasing, the use of English as a Lingua Franca is spread across the globe. English as a Lingua Franca enables the people who come from different background of language to communicate and interact with each other. It is important to study the use of English as a Lingua Franca in teaching English to Thai students as it fosters the teachers to be creative by employing different learning strategies in teaching English. This study aims to find out the beliefs and attitudes of the Indonesian teachers on the use of ELF in Thai context. Furthermore, this study aims to explore the factors which contribute to these beliefs and attitudes. The writers employed qualitative study by using closed-ended and open-ended questionnaires as well as interviews to collect the data. The findings indicated that there were three categories of beliefs which were found; they were: virtual, maximal, and optimal positions. The findings implied that for the Thai students with the poor level of English, mixing English and Thai was needed. Furthermore, there were also two factors which contribute to the shaping of the beliefs; they were: English learning experience and the English language identity.